The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.jpor.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two Ni–Cr dental alloys and the influence of casting mode on mechanical properties

Abstract: The Ni-Cr-Mo-Ti alloy showed high UTS, MHV and lowest EL comparaded with the tradicional Ni-Cr-Mo-Be, that show lowest UTS, MHV and higher EL when cast on induction/argon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
1
7
1
1
Order By: Relevance
“…Due to the different microhardness values of the alloys, the resultant roughness of this airborne particle abrasion may be different for each type of alloy. However, several studies have shown that some of these alloys have very close microhardness values (9,24,25) and in the present study, different bond strength values were found with the same resin cement.…”
Section: Resultscontrasting
confidence: 46%
“…Due to the different microhardness values of the alloys, the resultant roughness of this airborne particle abrasion may be different for each type of alloy. However, several studies have shown that some of these alloys have very close microhardness values (9,24,25) and in the present study, different bond strength values were found with the same resin cement.…”
Section: Resultscontrasting
confidence: 46%
“…This phase presumably has been formed via a solid state reaction during cooling and should correspond to the intermetallic NiBe phase, based on the work of Hero et al 14 . Thus, the presence of this very characteristic eutectic is also a microstructural evidence of beryllium in the Ni-Cr base alloys, in agreement with results found in other papers 12,[14][15][16] . Bauer et al 15 found a lamellar eutectic in the microstructure of a certain alloy and suggested the possible existence of Be in its composition, although the manufacturer claimed the absence of Be in that alloy.…”
Section: Resultssupporting
confidence: 92%
“…Sheet-like material samples with dimensions of 10 mm × 10 mm × 2 mm were prepared in accordance with the manufacturers’ recommendations using a laboratory lost wax technique [15]. Before corrosion testing, all samples were ground with 180-, 320-, and 600-grit Si carbide abrasive papers and then polished with 9-, 3-, and 0.05-μm diamond suspensions (Buehler, Germany) to produce mirror-like surfaces.…”
Section: Methodsmentioning
confidence: 99%